Innovation and Challenges in Funding Rapid Research Responses to Emerging Infectious Diseases: Lessons Learned from the Outbreak of Severe Acute Respiratory Syndrome - Bhagirath Singh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Although the local public health response to the severe acute respiratory syndrome outbreak in Canada was critical to the diagnosis, management and treatment of patients, such a rapid research response required a national effort to engage the research and stakeholder communities. The Canadian research effort, coordinated through the Institute of Infection and Immunity of the Canadian Institutes of Health Research and the Michael Smith Foundation for Health Research, has provided insight into the mechanisms required to ensure the rapid development of strategical initiatives in response to emerging infectious diseases. It has also provided a rational basis to set up a national network to be engaged if needed in the future.